Reading Capital: towards an understanding of the process of colonization in India - Shebl, Adham (AUC Knowledge Fountain, 2019)
This thesis examines the applicability of Karl Marx’s theoretical apparatuses in explaining the development of capital relations in India’s transition from commercial to industrial colonialism. Its findings engage with and are a response to the preponderance of secondary literature that argues against Marx’s usefulness in understanding the colonial moment in the Global South. Many of these secondary studies have argued against the use of Marx because of his purported Eurocentricity that renders his conclusions regarding the Global South inadequate. This study argues that fundamental to dissecting this intellectual argument is developing an understanding of Marx’s levels of generality whereby the historical descriptions and conclusions, and the theoretical framework and methods he employs are abstracted. To this end, this thesis asserts the levels of generality as the most critical to reading Marx as they permit the reader to move beyond the causal laws and tendencies and instead delve further into the relations that allow them to exist. Finally, this study shows how Marx’s totality of social life can be used to understand a particular society in a specific moment: India in the colonial period. While not all-encompassing, it shows the applicability of Marx’s theoretical apparatus to examine a colonized society — using India as an illustration — especially with regards to modes of production, social relations, and some aspects of legal and governmental arrangements. While further research would need to incorporate additional aspects of the social totality, including mental conceptions, reproduction of daily life, technology, and relationships to nature, its combination with the findings of the present study allows for a more complete view of capital relations in colonial India.